Static versus dynamic stretching; short term effects on physical performance in non-athletes- a randomized clinical trial - Shomaila Hassan Khan; Misbah Bin Ilyas; Jawad Ali; Zahid Mehmood; Raheela Kanwal; Arooba Sajjad; Kiran Khushnood (The Rehabilitation Journal, 2023)
Background: Non-athletes have varying fitness levels, muscle characteristics, and training backgrounds, which can affect how different types of stretching exercises impact their physical performance. Objective: to compare the acute effects of static and dynamic stretching on physical performance of non-athletes. A single-blinded, cross-over, randomized clinical trial was conducted at Iqra National University, Peshawar for a period of 6 months. A total of n=54 male participants were randomly allocated into group A and B. Group A performed the static stretching while group B performed dynamic stretching. The physical performance measure was endurance, agility, strength, flexibility, and balance respectively. Result: The result of two-way RMANOVA showed that both stretches had significant interaction effects between interventions and all performance measures (p<0.001) except for balance (p=0.23). The main effect showed that static stretching significantly reduced agility and balance (p<0.05), while dynamic balance improved all measures significantly (p<0.05). When comparing the mean differences of all variables, dynamic stretches showed significant improvement (p<0.05) in all variables as compared to static stretching. Conclusion: Dynamic stretch has a significant contribution to improving all physical performance measures among non-athletes if incorporated before the activity. While static stretching negatively affects the agility and balance among this population. (NCT05053490) Keywords: agility; balance; dynamic stretching; endurance; flexibility; non-athletes; physical performance; static stretching.